PENGARUH KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE OPPO PADA MAHASISWA SEMESTER SATU DI SEKOLAH TINGGI ILMU EKONOMI TENGGARONG - WARIANTO, ARIEF; ZAINUDDIN, MUHAMMAD (I-Con Media, 2021)
A lot of cellular phone products are present and sold in Indonesia. One of the most popular android smartphones today is the Oppo Smartphone. Since its inception in the world of mobile phones, Oppo has been known as a manufacturer that often sells its cellphone products at quite expensive prices but provides comparable quality and is no less quality than well-known manufacturer products so that it can compete in terms of bargaining power and purchasing decisions by new consumers. The purpose of this study was to determine the effect of product quality and promotion variables simultaneously and partially on purchasing decisions for Oppo smartphones by first semester students at STIE Tenggarong. The most dominant influence of variables on purchasing decisions in this study. The sample in this study were 30 people. The analytical tool used is multiple regression and testing the research hypothesis using the F test and t test. Simultaneously it shows that product quality and promotion have a significant influence on purchasing decisions on Oppo Smartphone purchases by the first semester students at STIE Tenggarong. Partially it shows that product quality and promotion have a positive and significant effect on purchasing decisions with a value of f 6960> f table 2.70. The most dominant variable in this study is product quality with t count 5,335> t table 1,628 while the promotion variable has t count 3,401> t table 1,628.Â